(3GdZQjH GdeUfas - (3GdbGSe Hf SdGe GdgQhj GdCROj GdNRGYj, CHh YHjO, J (B224 (3g` s
(3ChdgG (B:s
(3MOKfG CHh GdMSf WGgQ Hf YHO GdYRjR GdQYjfi bGd (B: (3bQCJ Ydi GHf YHO GdYRjR gPG GdZQjH GdeUfa hGdHhGOQ ef GdEfSGf hZjQg GddMeg GdJi Hjf GdefcH hGdYfb s
(3BNQgG (B:s
(3HGH ai GdJbOe ai GdSjQ (B: (3bGd CHh PDjH (B: ((3ahb GdfLe jJdYdY (B) (3hGdRe eKdg Re jRe hGdJegd (B: (3GdJbOe Je LejY GdOjhGf s
(3GdfSNI ajgG VHWs
(3fSNI NGeSIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B176 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B101s
Keywords: (3GddZIs